Pengaruh Loan Loss Provision, Financing Growth, Biaya Operasional dan Return on Asset Terhadap Non Performing Financing di Perbankan Syariah Indonesia - Hasepti Harizanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This article aims to determine the effect of specific variables namely LLP, FG, BOPO, and ROA at Bank Indonesia during the study period (2011-2016). The number of samples in this study was 12 Islamic banks using purposive sampling techniques. This study uses panel data regression analysis, with some chow test model selection, Hausman test, Lagrange multiplier test, and hypothesis testing using a T-test to test the regression coefficients partially and the F-test to test the effect together at a significant level 5%. The results obtained in this study are Loan Loss Provision (LLP), Financing Growth (FG), Operational Costs (BOPO), have a positive and significant effect on NPF. While the Return on Assets (ROA) has a positive and not significant effect on NPF. But together the independent variables have an effect on NPF Islamic Banks in Indonesia.